The Image Map Survey of High School Students for Tokyo Metropol Area - How They Perceive Their Urban Environment - Hattori, Keiro (AESOP, 2015)
In order to execute a good urban planning, one should understand how people However, most of Japanese cities have tendency to neglect how people conceive neglect is even stronger toward teenagers, thus making most of Japanese cities. In order to make up for these situations, the research is conducted in order to school students living in Tokyo perceive their city. The research has applied Map Study and asked 192 high school students to draw the map of Tokyo. Findings of the research are as follow. 1) Most of high-school students perceived spatial structure of Tokyo with train lines. 2) Most important train line for high school students to image Tokyo is Yamanote-that connects important nodes of Tokyo. 3) 142 students (74%) drew the municipal boundary of Tokyo Metropolitan Gove maps had the correct shape of Tokyo. 4) Many maps did not have landmarks. Comparing to the number of maps that drew the number of maps that drew landmarks were much less. The study result suggests that high-school students have a strong tendency to spatial structure with train nodes and train paths. In order to make Tokyo mor higher sense of place for younger generations, it is recommended to improve accessibility stations and train paths should be considered more seriously in enhancing its addition, the lack of landmarks makes Tokyo very difficult to image spatial structure of landmarks should be enhanced as well as creating new landmarks with a strong
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015